2019
DOI: 10.1002/ecs2.2820
|View full text |Cite
|
Sign up to set email alerts
|

Positive plant–plant interactions expand the upper distributional limits of some vascular plant species

Abstract: ETH Z€ urich, Z€ urich 8092 Switzerland Citation: Raath-Kr€ uger, M. J., M. A. McGeoch, C. Sch€ ob, M. Greve, and P. C. le Roux. 2019. Positive plant-plant interactions expand the upper distributional limits of some vascular plant species.Abstract. Biotic interactions can shape species' distributions through their impact on species' realized niches, potentially constraining or expanding the range of conditions under which species occur. We examine whether fine-scale plant-plant interactions scale up to shape b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
(109 reference statements)
1
14
0
Order By: Relevance
“…We showed that the persistence of the subtidal macroalga, H. incurva , and its ability to support invertebrate biodiversity in shallow‐water habitats rely upon light stress reduction by the epiphytic coralline alga, J. rubens . Thus, our work, together with previous studies in terrestrial and intertidal systems (Afkhami et al., 2014; He & Bertness, 2014; He & Cui, 2015; Peterson & Bell, 2012; Raath‐Krüger et al., 2019), provides evidence for the critical role of facilitation in shaping patterns of species distribution and acting as a structuring force of communities across multi‐trophic levels.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We showed that the persistence of the subtidal macroalga, H. incurva , and its ability to support invertebrate biodiversity in shallow‐water habitats rely upon light stress reduction by the epiphytic coralline alga, J. rubens . Thus, our work, together with previous studies in terrestrial and intertidal systems (Afkhami et al., 2014; He & Bertness, 2014; He & Cui, 2015; Peterson & Bell, 2012; Raath‐Krüger et al., 2019), provides evidence for the critical role of facilitation in shaping patterns of species distribution and acting as a structuring force of communities across multi‐trophic levels.…”
Section: Discussionsupporting
confidence: 78%
“…Few studies, however, have assessed how small‐scale positive interactions may scale up to regulate species distribution at broader scales (e.g. landscape or regional scales; but see Afkhami et al., 2014; Raath‐Krüger et al., 2019; Uyà et al., 2019). For example, in terrestrial systems, mutualistic endophytic fungi can expand the geographic range of their grass host by thousands of square kilometres towards drier regions (Afkhami et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In more recent floristic surveys on the island, R . moseleyi has not been found (Raath-Krüger et al 2019, P. le Roux, personal communication 2020), and the species was left off a recent plant list for Marion Island (Chau et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many parameters can be applied to quantify plants interactions (Weigelt and Jolliffe, 2003), where relative competition intensity (RCI) is a widely used one. Previous studies found that plant interactions vary with species identity (Catorci et al, 2011;Raath-Krüger et al, 2019) and their growing stages (Yang and Rudolf, 2010;. Plant interaction at the early growing stage is crucial for plant establishment in plant populations and communities (Lortie and Turkington, 2008;Hart et al, 2018), and warrants more research.…”
Section: Introductionmentioning
confidence: 98%